2022
DOI: 10.3389/fendo.2022.939048
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Capecitabine to Adjuvant Chemotherapy May be the Most Effective Strategy for Patients With Early-Stage Triple-Negative Breast Cancer: A Network Meta-Analysis of 9 Randomized Controlled Trials

Abstract: Background and ObjectivePrevious studies determined the therapeutic effects of capecitabine-based chemotherapy regimens on early-stage triple-negative breast cancer (TNBC). However, the optimal strategy of capecitabine-based chemotherapy remains uncertain. We conducted this network meta-analysis to address this issue.MethodsWe systematically searched PubMed, Embase, and the Cochrane Registry of Controlled Trials (CENTRAL) to retrieve eligible studies published before September 2021. Two independent reviewers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…30 Capecitabine, when added to adjuvant chemotherapy, prolongs disease-free and overall survival in triple negative breast cancer patients as compared to standard therapy. 31 There is also emerging evidence that the addition of immunotherapy, such as PD1/PD-L1 inhibitors, to the treatment regimen may benefit patients with early-stage or advanced triple negative breast cancer. 32 For example, the addition of pembrolizumab to other neoadjuvant chemotherapy in patients with stage II− III TNBC, as reported in the KEYNOTE-522 clinical trial, results in a higher pathologic complete response at the time of surgery and reduced disease progression and recurrence as compared to patients who do not receive pembrolizumab over a median follow up period of 15.5 months.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Capecitabine, when added to adjuvant chemotherapy, prolongs disease-free and overall survival in triple negative breast cancer patients as compared to standard therapy. 31 There is also emerging evidence that the addition of immunotherapy, such as PD1/PD-L1 inhibitors, to the treatment regimen may benefit patients with early-stage or advanced triple negative breast cancer. 32 For example, the addition of pembrolizumab to other neoadjuvant chemotherapy in patients with stage II− III TNBC, as reported in the KEYNOTE-522 clinical trial, results in a higher pathologic complete response at the time of surgery and reduced disease progression and recurrence as compared to patients who do not receive pembrolizumab over a median follow up period of 15.5 months.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The absence of surface receptor expression has led to the search for new therapeutic options . Capecitabine, when added to adjuvant chemotherapy, prolongs disease-free and overall survival in triple negative breast cancer patients as compared to standard therapy . There is also emerging evidence that the addition of immunotherapy, such as PD1/PD-L1 inhibitors, to the treatment regimen may benefit patients with early-stage or advanced triple negative breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy methods, integrating antineoplastic agents, are increasingly adopted to enhance treatment results ( 54 ). Antineoplastic combined chemotherapy protocols have proven to be particularly valuable in managing hormone receptor-positive breast cancers ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In earlystage TNBC patients, capecitabine in combination with standard adjuvant chemotherapy showed significant disease-free survival and overall better survival outcomes than standard chemotherapy with tolerable adverse events [24]. A study showed that the addition of capecitabine-based chemotherapy was the most effective regime [25].…”
Section: Conventional Chemotherapymentioning
confidence: 99%